Класифікація витрат у розрізі складових людського капіталу як передумова розвитку методології бухгалтерського обліку - Давидюк, Тетяна Вікторівна (Запорізький національний університет, 2012)
У статті запропоновано класифікацію витрат, виходячи з положень теорії людського капіталу, у розрізі складових людського капіталу, в основу якої покладено фази його життєвого циклу (витрати на формування, використання та відтворення), що забезпечує систематизацію релевантної інформації в необхідних аналітичних розрізах і сприяє розвитку методології бухгалтерського обліку в частині відображення таких витрат на рахунках.

Classification of expenses has been suggested stemming from the statements of the human capital theory from the point of human capital constituents, the basis for which is the phases of its life cycle (expenses on formation, utilization and renewal), which secures the systematization of relevant information in the necessary analytical sections and assists in the development of accounting methodology in the part of reflection such kind of expenses on accounts.
Classification of expenses from the standpoint of human capital constituents as a prerequisite of accounting methodology development
Keywords: людський капітал; теорія людського капіталу; бухгалтерський облік; витрати; human capital; theory of human capital; accounting